Indonesia Meta Analisis Pengaruh Model Pembelajaran Realistic Mathematics Education (RME) Untuk Meningkatkan Hasil Belajar Matematika - Safitri, Vivi Irvana; Caswita, Caswita; Rumite, Wayan; Afifah, Nadia Zahra (Mandalika Mathematics and Educations Journal, 2024)
This research aims to re-analyze the effectiveness of the Realistic Mathematical Education (RME) model on students' learning outcomes. The study employs a meta-analysis method using qualitative descriptive analysis, reviewing articles from previously published research. A total of 20 national articles accessible online through Google Scholar, published between 2019 and 2024, were sampled. The search for articles was conducted using the Publish or Perish application with the keywords “Realistic Mathematical Education (RME)” and “Learning Outcomes.” This meta-analysis utilized 20 relevant articles from national journals regarding Realistic Mathematical Education (RME) and its impact on students' learning outcomes from 2019 to 2024.The results of the meta-analysis indicate that this model can improve students' learning outcomes, with a minimum increase of 0.07% and a maximum increase of 0.74%, resulting in an average percentage increase of 0.466%. The effect size calculated was 0.1523, categorized as having a moderate influence. Therefore, it can be concluded that the Realistic Mathematical Education (RME) model is highly effective in mathematics instruction for enhancing students' learning outcomes.